2012
DOI: 10.1021/om300550k
|View full text |Cite
|
Sign up to set email alerts
|

Iridium(III) Cp* Complexes for the Efficient Hydroamination of Internal Alkynes

Abstract: A series of iridium(III) and rhodium(III) 1,2,3,4,5-pentamethylcyclopentadienyl (Cp*) complexes of the type [M(Cp*)(LL)Cl]BPh 4 were synthesized, where LL is a chelating diimine or mixed pyrazolyl-phosphine or pyrazolyl-N-heterocyclic carbene donor ligand. The majority of these complexes were characterized by X-ray crystallography, allowing for a detailed comparison of their structural properties. These complexes were shown to yield active hydroamination catalysts upon in situ abstraction of the chloride colig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Rh(I)/Rh(III) and Ir(I)/Ir(III) complexes have been demonstrated by us and others to be efficient catalysts for this transformation. 12,20,32,[40][41][42][43][44][45][46][47][48] We have found that small variations in donor ability of the ligands can lead to significant variations in the catalytic efficiency of the resulting metal complexes. 32,41,49 We tested a number of the Rh(I), Rh(III) and Ir(III) complexes containing the NHC-1,2,3-triazolyl donor ligands described here as catalysts for the intramolecular hydroamination of 4-pentyn-1-amine to form 2-methyl-1-pyrroline (Table 3).…”
Section: Catalysismentioning
confidence: 96%
See 2 more Smart Citations
“…Rh(I)/Rh(III) and Ir(I)/Ir(III) complexes have been demonstrated by us and others to be efficient catalysts for this transformation. 12,20,32,[40][41][42][43][44][45][46][47][48] We have found that small variations in donor ability of the ligands can lead to significant variations in the catalytic efficiency of the resulting metal complexes. 32,41,49 We tested a number of the Rh(I), Rh(III) and Ir(III) complexes containing the NHC-1,2,3-triazolyl donor ligands described here as catalysts for the intramolecular hydroamination of 4-pentyn-1-amine to form 2-methyl-1-pyrroline (Table 3).…”
Section: Catalysismentioning
confidence: 96%
“…The M-C* (Table 2) are within the range reported in the literature for analogous Rh(III) and Ir(III) complexes with Cp* co-ligands. 12,32,[35][36][37][38][39] The M-C2 bond in complexes 4b, 4d and 5b with the small methyl substituent on the imidazolyl ring is significantly shorter than the equivalent bond in the analogous complexes with the mesityl substituent 4a, 4c and 5a ( Table 2). The longer M-C2 bond in complexes with a mesityl substituent is likely to be due to steric repulsion between the Cp* and the bulky mesityl group.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Such compounds with chelating nitrogen ligands are effectively used in catalysis, e. g. in water oxidation [23], intramolecular hydroamination of alkynes [24], Diels-Alder reactions [25], asymmetric Michael addition reactions [26], asymmetric hydrogenation [27,28], and transfer hydrogenation [29][30][31], reactions of ketones and imines.…”
Section: Scheme 1 Reaction Conditions In Transfer Hydrogenation Of Amentioning
confidence: 99%
“…The formerly unknown precursor complexes with methyl 2,3-diamino-4,6-O-benzylidene-2,3-dideoxy-␣-D-hexopyranosides (compounds 1-4, Chart 1), methyl 2-amino-4,6-OChart 1. Diaminomonosaccharides 1-4, methyl 2-amino-4,6-O-benzylidene-2,3-dideoxy-3-tosylamido-␣-D-glucopyranoside (5) and corresponding diamino derivatives (S)-2,2 -diamino-1,1 -binaphthalene (6) and (R,R)-1,2-diphenylethylenediamine (7) and their halfsandwich complexes of iridium(III), -rhodium(III) and ruthenium(II) (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) for transfer hydrogenation ([T-4-R] and [T-4-S] denote the absolute configuration of the metal center in a pseudo-tetrahedral environment following the CIP rules).…”
Section: Introductionmentioning
confidence: 99%